EFFICACY OF NEW FORMULATION OF CHLORPYRIPHOS AGAINST RICE HOPPER PESTS VIS-A-VIS EFFECT ON NATURAL ENEMIES IN IRRIGATED RICE ECOSYSTEM OF WEST BENGAL - SATPATHI, C.R.; RAUT, A.M.; MONDAL, A.; CHIHATRAPATI, KETAN (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2016)
An experiment was conducted to evaluate bioefficacy of a new formulation of chlorpyriphos 20% CS for the control of brown plant hopper, green leafhopper and white backed plant hopper on paddy crop in Gangetic alluvial zones of West Bengal during 2014 and 2015. Chlorpyriphos 20% CS (a) 375 and 500 ga.i./ha offered better crop protection against all the three pests and resulted in higher grain yield. Imidacloprid 17.8% SL (a) 25 ga.i/ ha and fipronil 5% SC (a 75 ga, i/ ha were also found equally effective against hopper pests. Besides controlling the hopper pests, all these treatments showed no adverse effect on the natural enemies particularly Spiders (Phidippus sp., Oxyopes javanus, O. lineatipes and Lycosa pseudoannulata) and damselfly (Agriocnemis femina femina, A. pygmaea pygmaea, Ceriagrion sp., Ischnura aurora aurora and I. senegalensis). The above treatments and also chlorpyriphos 20% CS (a) 1000 ga.i./ha showed no phytotoxic symptoms on the paddy crop.